Щодо питання вдосконалення гірничої наукової термінології - Кокоулін, І.Є. (Геотехническая механика, 2012)
Сформулированы основные подходы к анализу существующей в горной науке Украины терминологии. Показано, что в ряде случаев неправомерно использовать термины, просто заимствованные из других языков; в то же время следует соблюдать корректность при формулировке новых понятий и определений с учетом особенностей построения слов и грамматических конструкций в украинском языке. The basic approaches to the analysis of existing in a mountain of Sciences of Ukraine terminology. It is shown that in some cases, improperly use the terms, simply borrowed from other languages;at about the same time, it should comply with the correctness of the wording of new concepts and definitions, allowing for the construction of words and grammatical constructionsments in the Ukrainian language.